Morphometric discrimination among four species of the Mysis relicta group - Vainola, R; Audzijonyte, A; Riddoch, BJ (Fundamental and Applied Limnology, 2002)
Mysid crustaceans of the Mysis relicta group play central roles in many fresh- and brackish-water ecosystems both in northern Eurasia and North America. Yet, the recent division of the taxon into four sibling species by molecular criteria has largely remained unnoticed in ecological studies. We illustrate the morphometric differences among these species and the feasibility of their practical discrimination using multivariate analyses of 31 metric and meristic traits. The main patterns of size-independent variation identified in principal component analysis of individuals and in canonical variate analysis of populations corresponded to their assignment to the allozymically delineated species. The main variables contributing to discrimination described the spines or setae of the telson, uropods and maxillae, and the shape of the telson cleft. The subarctic sp. III was the phenetically most distinct from the others. The European stenohaline sp. I appeared intermediate between the North American freshwater sp. IV and the European euryhaline sp. II. In discriminant analyses between individual species pairs, 97-100 % correct identification was obtained using 3 -10 characters. The discriminant function for sp. I vs. sp. II, whose distributions overlap in northern Europe, was tested with independent material, and found to be a reliable means of species identification both at population level and at individual level in sympatric populations.